2003
DOI: 10.1128/cdli.10.1.30-37.2003
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immunoresponses in Mice after Repeated Exposure of Lungs to Spores of Streptomyces californicus

Abstract: Microbial growth in moisture-damaged buildings is associated with respiratory and other symptoms in the occupants. Streptomyces spp. are frequently isolated from such buildings. In the present study, we evaluated the responses of mice after repeated exposure to spores of Streptomyces californicus. Mice were exposed via intratracheal instillation to six doses (at 7-day intervals) of the spores of S. californicus, originally isolated from the indoor air of a moisture-damaged building, at three dose levels (2 ؋ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
0
20
1
Order By: Relevance
“…Torvinen et al [57] also described different potential pathogenic Mycobacteria isolated from water damaged building materials. Mycobacteria species are known to be responsible for different negative health effects, such as infections, inflammatory response, production of cytokines, NO and IL6 [ 16,21] and hypersensitivity pneumonitis [7,9]. In the present study, seven different Mycobacterium species were detected.…”
Section: Discussionmentioning
confidence: 50%
“…Torvinen et al [57] also described different potential pathogenic Mycobacteria isolated from water damaged building materials. Mycobacteria species are known to be responsible for different negative health effects, such as infections, inflammatory response, production of cytokines, NO and IL6 [ 16,21] and hypersensitivity pneumonitis [7,9]. In the present study, seven different Mycobacterium species were detected.…”
Section: Discussionmentioning
confidence: 50%
“…6,7 Likewise, investigators have observed the same phenomenon among pigeon breeders and farmers who experienced no clinical deterioration despite continued IA exposure. [8][9][10] We believe the contrasts in the literature 11,12 refl ect the complex pathogenesis of HP and that the HP phenotype that develops likely hinges on multiple factors, including the type of IA, extent of exposure, and, perhaps most The following variables were backward eliminated from the full model: interaction between pulmonary fi brosis and IA exposure, sex, and ATS dyspnea score. See Table 1 bias to our tertiary care center, our program likely evaluates and cares for a greater proportion of patients with fi brotic HP than most community practices; however, subjects in this cohort appear representative of the general population of patients with chronic HP.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, a single large dose of spores of S. californicus, a sporulating bacterium isolated from the air inside damp buildings, induced acute inflammatory changes in mouse lungs [41]. A recent study indicated that systemic immune system changes occurred at lower doses than pulmonary inflammation in mice after 6 weekly doses of S. californicus at lower concentrations [42 ]. The ability of these or other extra-pulmonary effects of bioaerosols to explain the systemic symptoms of SBS remains to be seen, but the results indicate the need for further study of these effects at low doses of relevant bioaerosols.…”
Section: Toxicologymentioning
confidence: 97%